Degradation of external quantum efficiency of AlGaN UV LEDs grown by hydride vapor phase epitaxy. Issue 4 (23rd January 2015) - Shmidt, Natalia; Usikov, Alexander; Shabunina, Eugenia; Chernyakov, Anton; Sakharov, Alexey; Kurin, Sergey; Antipov, Andrei; Barash, Iosif; Roenkov, Alexander; Helava, Heikki; Makarov, Yuri
Abstract: A comparative study of the degradation of HVPE‐grown 360 nm AlGaN/GaN UV and commercially available InGaN/GaN blue LED chips was performed. The common feature of the degradation of these two types of LEDs was found to be the increase of the conductivity of shunt paths under current injection. The paths (shunts) are localized in the extended defects system (EDS). It is proposed that the conductivity increase is due to defect formation under multiphonon carriers recombination in a part of the EDS enriched by Ga or In atoms. This process is accompanied by a local overheating and migration of Ga or In atoms. To increase the lifetime of the AlGaN/GaN UV LEDs to more than 2000 h it is necessary to improve their nano‐structural and nanoscale AlGaN composition ordering. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)